1152 Collecting and organising basic occupational health data for international comparisons. (24th April 2018) - Tsutsumi, A; Kajiki, S; Muto, T; Shimazu, A; Okahara, S; Ohdo, K; Yoshikawa, T; Mishiba, T; Inoue, A
Abstract : Introduction: In regard to international research on occupational health, field survey reports concerning occupational health institutions and related professionals overseas have increased, resulting in an increased number of international comparative studies. However, obtaining mortality and sick leave statistics as well as basic data on industrial accidents overseas still remain difficult because these data have never been collected or, if they have been collected, have never been organised. A research group has been launched to collect basic data, including the above-mentioned data, of as many countries as possible as well as organising the data. The aim of the study is to obtain knowledge that will develop into international comparative studies. Methods: The steps we are taking consist of collecting new data and information that the ILO, WHO and other international organisations and Japanese research institutes possess or have published, combining these with the data and information held by Japanese occupational health researchers as well as the results of bibliographic searches, and comparing these with the data of other countries and showing them in an organised form. Results: We have made the lists to be collected as follows and started to collect the data with the worldwide base: Occupational disease statistics (by industry, disease and year) Mortality statistics due to industrial accidents Off–the–job injury and sickness statistics (with necessary definitions) Implementation status of health examinations and special health examinations (if actually performed), together with examination items and the rate of abnormal findings Actual benefit payment under industrial accident compensation insurance (if there is an insurance plan or similar system) Suicide statistics Actual management of chemical substances Other necessary points in your survey of worker health in your country Have any industrial accident prevention plans or similar programs been established by the government? If so, what are the rates of accomplishment and achievement of the plans? Statistics related to the basic work force of your country. The preliminary findings include that there are no systematic registries on some occupational diseases statistics even in industrialised countries, and for international comparison it is necessary to get the information on how to collect statistics which may vary between countries. Conclusion: Our research will enable having basic knowledge that contributes to improving occupational health standards. Simultaneously, we intend to summarise our work, recommending the benefits of using these basic data, and indicating matters requiring further solutions and the prospects for international comparisons. The results will be published on our website for general use and in scientific journals. Acknowledgement: This research is supported by the Occupational Health Promotion Foundation of Japan.